The Exchange Rate Exposure of a Global Competitor - Luehrman, Timothy A. (Journal of International Business Studies, 1990)
This paper analyzes the exposure of operating cash flows to an exogenous exchange rate change for a firm operating internationally as a multimarket oligopolist (i.e., a “global” competitor) and facing demand that depends in a general way on the exchange rate. It is shown that exposure is the sum of a base case exposure identified in other studies and two other components: terms associated with exchange rate-induced demand shifts and terms associated with competitors's reoptimization following the exchange rate shock. In general, the magnitudes of these additional terms are significant, especially in the presence of asymmetries across markets and firms. Numerical examples are provided that incorporate asymmetries corresponding to stylized facts about some U.S. markets and U.S. manufacturers.